Mapping meanings of corporate social responsibility: An Australian case study - Anne Elizabeth Fordham; Guy Martin Robinson (International Journal of Corporate Social Responsibility (JCSR), 2018)
Corporate Social Responsibility (CSR) is an evolving concept that reflects various views and approaches regarding corporate relationships with broader society. This study examines the meanings and values attached to CSR within the Australian resource sector where various interests shape the implementation of CSR programs. The study was based on in-depth interviews with industry practitioners, business leaders, environmental and social specialists, government representatives and community leaders, including representatives from Indigenous groups.CSR was found to be a complex, multi-dimensional concept that was highly individualised with a variety of aspects highlighted during interviews. To make sense of this complexity, meanings of CSR were mapped according to Carroll's four dimensions, namely Corporate, Legal, Ethical, and Philanthropic. However, a further CSR dimension was also required to capture the full spectrum of meanings. Referred to as "CSR interaction", this dimension focuses on CSR meanings that align with the concept of CSR creating social change and improving the dynamics between companies and local communities and stakeholders.This study also identified some key social processes or drivers which helped explain how and why CSR meanings and approaches are adopted and delivered. These drivers also increased understanding of the wide diversity of CSR meanings and their distribution across the different stakeholder groups. Drivers included not only individual-level influences such as background, life experience, cultural and ethical values, but also broader influences such as organisational and institutional context. The implications of this for CSR practice were explored.The study sought to provide guidance for developing a working definition of CSR within the given context, through identifying the key integral requirements for CSR incorporating different perspectives and interests. The intent is that this can help support evaluation of the future success of CSR programs within the Australian resource sector.
Keywords: 650; Community development; Corporate social responsibility; Ethics; Resource development; Sociology; Stakeholder engagement; Sustainable development